The First Record of Three Monogenean Species of Gyrodactylus in Iraq from Gills of Some Fishes in Tigris River, Al-Shawwaka Region, Baghdad Province - Al-Saadi, Abid Ali J. J.; Rasheed, Rabab A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Three monogenean species of the genus Gyrodactylus viz. G. cotti Roman, 1956 on gills of Planiliza abu, G. mikailovi Ergens & Ibragimov, 1976 on gills of Chondrostoma regium and G. prostae Ergens, 1963 on gills of Alburnus caeruleus were recorded from Tigris river at Al-Shawwaka region, Baghdad. The description and measurements of these parasites as well as their illustrations where given. All these parasites are recorded here for the first time in Iraq.